Developmental patterns of adolescent spiritual health in six countries. (December 2016) - Michaelson, Valerie; Brooks, Fiona; Jirásek, Ivo; Inchley, Jo; Whitehead, Ross; King, Nathan; Walsh, Sophie; Davison, Colleen M.; Mazur, Joanna; Pickett, William; ,
Abstract: The spiritual health of adolescents is a topic of emerging contemporary importance. Limited numbers of international studies provide evidence about developmental patterns of this aspect of health during the adolescent years. Using multidimensional indicators of spiritual health that have been adapted for use within younger adolescent populations, we therefore: (1) describe aspects of the perceptions of the importance of spiritual health of adolescents by developmental stage and within genders; (2) conduct similar analyses across measures related to specific domains of adolescent spiritual health; (3) relate perceptions of spiritual health to self-perceived personal health status. Cross-sectional surveys were administered to adolescent populations in school settings during 2013–2014. Participants ( n =45, 967) included eligible and consenting students aged 11–15 years in sampled schools from six European and North American countries. Our primary measures of spiritual health consisted of eight questions in four domains (perceived importance of connections to: self, others, nature, and the transcendent). Socio-demographic factors included age, gender, and country of origin. Self-perceived personal health status was assessed using a simple composite measure. Self-rated importance of spiritual health, both overall and within most questions and domains, declined as young people aged. This declining pattern persisted for both genders and in all countries, and was most notable for the domains of "connections with nature" and "connections with the transcendent". Girls consistently rated their perceptions of the importance of spiritual health higher than boys. Spiritual health and its domains related strongly and consistently with self-perceived personal health status. While limited by the 8-item measure of perceived spiritual health employed, study findings confirm developmental theories proposed from qualitative observation, provide foundational evidence for the planning and targeting of interventions centered on adolescent spiritual health practices, and direction for the study of spiritual health in a general population health survey context. Highlights: Spiritual health is recognized as one of four domains of health. Few quantitative studies exist describing patterns of spiritual health in child populations. We employed a series of items that describe perceptions of the importance of spiritual health and its domains in adolescents. We demonstrated strong developmental and gender-based patterns that were consistent across countries and cultures. Perceptions of the importance of spiritual health appear to be linked with adolescent health outcomes.